Gambaran Pengetahuan dan Sikap tentang Menggosok Gigi yang Benar pada Siswa SDN Sungai Tiung 3 Cempaka - Muhammad Doni Alfiannor; Evy Marlinda; Sugian Noor (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2018)
Oral hygiene is very important because through these organs various germs can enter. Some mouth problems can also occur due to lack of maintaining dental and oral hygiene. The remaining food that is not cleaned by the method of brushing your teeth properly will be difficult to clean and will become a collection of dental plaques (dental caries) and consequently can cause cavities. This study aims to get an overview of the knowledge and attitudes about brushing teeth properly in students of SDN 3 Sungai Tiung Cempaka. The research design used was descriptive. The number of respondents was 32 people with sampling using the total sampling technique. Data collection using a questionnaire. The results showed that most respondents had enough knowledge as many as 17 people (53.1%) and most respondents had a positive category attitude of 27 people (84.4%). It is expected that the health center participates in providing treatment to improve children's health status, especially dental and oral health